2014
DOI: 10.1073/pnas.1409485111
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CD112 by the alphaherpesvirus gD protein suppresses DNAM-1–dependent NK cell-mediated lysis of infected cells

Abstract: Significance Herpesviruses have developed fascinating mechanisms to evade elimination by key elements of the host immune system, allowing these pathogens to cause lifelong infections with periods of recurrent virus spread. Natural killer (NK) cells are central in the innate antiviral response. Here, we report that the gD glycoprotein of the alphaherpesviruses, pseudorabies virus and herpes simplex virus-2, displays previously uncharacterized immune evasion properties toward NK cells. Expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 51 publications
5
65
0
Order By: Relevance
“…Second, gD might perform essential in vivo functions, such as suppression of NK cell-mediated lysis of infected cells (48) or modulation of innate antiviral responses (49). We propose that B virus evolutionarily selected for a unique gD-independent entry mechanism while still maintaining the ability to use gD-mediated pathways, in view of our data presented here.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Second, gD might perform essential in vivo functions, such as suppression of NK cell-mediated lysis of infected cells (48) or modulation of innate antiviral responses (49). We propose that B virus evolutionarily selected for a unique gD-independent entry mechanism while still maintaining the ability to use gD-mediated pathways, in view of our data presented here.…”
Section: Discussionmentioning
confidence: 68%
“…After adsorption at 37°C for 1 h, the cell monolayers were rinsed with PBS, overlaid with 1 ml of medium (set as 0 h on the time scale), and returned to a 37°C humidified incubator (5% CO 2 ). At selected time points (0, 4,8,12,24,48, and 72 h postinfection [p.i. ]), infected cells were harvested by placing the plates on dry ice, followed by a short freeze-thaw procedure and scraping the cells into medium.…”
Section: Virusesmentioning
confidence: 99%
“…Nectin-2 is also a ligand of the activating natural killer (NK) cell receptor DNAX accessory molecule 1 (DNAM-1) (43,(89)(90)(91)(92). Work in PRV and HSV-2 showed that following cellular transfection with gD or viral infection, DNAM-1 was downregulated to prevent NK cell-mediated cytolysis of infected cells (93). Because B virus can interact with nectin-2, B virus may have a similar mechanism to evade NK cell-mediated cytolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the interaction of DNAM-1 with one of its ligands, CD112, is a pathogenic target of herpesvirus, in which a viral gene product (gD) stimulates degradation of CD112 to avoid NK-cell-mediated lysis of infected cells and subsequent viral clearance. 25 Similarly, HIV infection drives an exhausted T-cell phenotype, characterized by loss of DNAM-1 expression. 26 In line with a central role for DNAM-1 in cancer immunosurveilance, genetic evidence has emerged implicating DNAM-1 mutations as a significant cancer risk factor.…”
Section: Introductionmentioning
confidence: 99%